Implementation of Language Attitude and Turn-Taking of the Guest Star at Talk Show - Melda Veby Ristella Munthe; Asima Rohana Sinaga; Mungkap Mangapul Siahaan (Jurnal Pendidikan, Sains Sosial, dan Agama, 2022)
This research is conducted in order to find out, namely: (1) The ways of Guest Star implement their Language Attitude during giving comments about the questions made by Andy, (2) The ways of Guest Star implement their Turn-Taking during giving comments about the questions made by Andy, and (3) The reason of Guest Star behave as the way they are in giving comments. The research method applied for this research is qualitative research. Instrument used to gather the data is the record of the conversation between Andy and Guest Star in the TV talk show. The writer analyzed the data then categorized into the components of Language Attitude and a framework for Turn-Taking. The findings of the research, namely: (1) It occurred dominantly applied the Affective Component on the utterances of them, and (2) The Guest Star gave their individual’s perception upon their responds. The Guest Star arranged their thought, opinion, suggestion, emotion, belief and action